1001 guitars to dream of playing before you die - Burrows, Terry (London Cassell Illustrated, 2013)
A visually stunning reference guide that traces the evolution of the most inflentual instrument of the last century.
Includes index.
Keywords: Guitar -- History -- Pictorial works; Guitar